PERAN PERUMUSAN MASALAH DAN TINJAUAN PUSTAKA DALAM MENJAMIN KUALITAS PENELITIAN ILMIAH - Putri Norlayli Mustakim; Uci Fadillah; Siti Khairani Arfandi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Problem formulation and literature review are pivotal methodological elements in scientific research that contribute to the study’s methodological and scholarly quality. Problem formulation determines research focus and direction, while literature review provides theoretical foundations and identification of research gaps (Rahman et al., 2025; Ebidor & Ikhide, 2024). This study used a qualitative approach with a library research design and content analysis to review literature regarding the role of these components in ensuring research quality. Findings indicate that clear problem formulation supports methodological consistency and clarity of objectives, while comprehensive literature review strengthens theoretical grounding and helps identify relevant research gaps. Their integration significantly enhances focus, relevance, and validity of scientific research.